Management of Gastrointestinal Cutaneous Fistulae. - Alobaidi, Munthir A. A. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: -Gastrointestinal cutaneous fistula G.I.C.F. occur either postoperative or spontaneous, it is a major complication to patients & surgeons together,, still have significance incidence of morbidity’ & mortality.& it needs specific management.Ainu-To study the causes of the fistula, to study the methods of treatment either medical or surgical with or without the use of total parenteral nutrition. T.P.N.Patients& methods: -a prospective study done on 61 patients, divided into male &female, patients. G.I.C.F.were divided into high output & low output fistulae, then an attempt to find the causes of the fistulae & the type of treatment both conservative &surgical treatment, also to study the effect of the use of T.P.N.Result:-45 patients were male &16 were female. Age range 13—58 years. The most common cause of the fistula M’as missile injury 39(63.93%)patients, followed by iatrogenic 6 (9.83%) then carcinoma of colon 6(9.83%).59(96.72%) patients developed fistula postoperative, & only 2(3.27%) patients developed the fistula spontaneous. The most common site of the fistula M’as the ileum 22(30.06%) patients; the least common site M’as the esophagus 2(3.27%).32 (52.45%) patients were with high output fistula. 29(47.54%) patients were with low output fistula. Spontaneous closure rate M’as 57.37%, total number of patients treated by conservative methods were39, while the total number of patients treated by surgery were22.89.74% closure rate by conservative treatment, closure rate by surgical treatment were63.63%..The mortality rate M’as 12 (19.67%) patients.Conclusion: -spontaneous closure rate of the fistula is high, the conservative treatment gave higher closure rate than the surgical treatment. The use of T.P.N.& octreotide decrease the morbidity & mortality.